1996
DOI: 10.1016/0014-5793(96)00659-x
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of nitrite, a stable product of nitric oxide (NO) formation, on arginase

Abstract: Macrophages contain arginase and an inducible NO synthase, demonstrated by using L-arginine, the common substrate, for production of both nitric oxide and urea. Arginase was inhibited by nitrite, the stable end product of NO. This inhibition was non-competitive, and could not be explained by the reaction of nitrite with arginine, or by the irreversible covalent modification of arginase, or by the removal of Mn 2+, a cofactor of arginase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Recent studies have reported that arginase modulates NOS activity via arginine consumption (17,34). On the other hand, it has been reported that arginase is inhibited by the nitrite, a stable end product of NO (35). We demonstrated a negative correlation between seminal plasma NO level and arginase activity during stress.…”
Section: Discussionsupporting
confidence: 53%
“…Recent studies have reported that arginase modulates NOS activity via arginine consumption (17,34). On the other hand, it has been reported that arginase is inhibited by the nitrite, a stable end product of NO (35). We demonstrated a negative correlation between seminal plasma NO level and arginase activity during stress.…”
Section: Discussionsupporting
confidence: 53%
“…For example, in macrophages, high concentrations of NOS-derived NO feedback to switch off NOS activity [29]. The ornithine product spermine, can inhibit NOS activity [30] and nitrite, the stable metabolite of NO, can suppress arginase activity [31]. Therefore the activity of these two enzyme systems, under normal conditions, would be mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…To date there are no data, however, on the interaction and competition of these two alternate pathways and their effects on wound healing. It should be noted that L-hydroxy-arginine and nitrite, the intermediate and end products, respectively, of NO synthesis, are both strong arginase inhibitors (Hrabak et al, 1996). Furthermore, urea, the end product of arginase activity, inhibits NO formation (Okuno et al, 2004).…”
Section: Chemistry Of Nitric Oxidementioning
confidence: 99%